Pengaruh Beberapa Dosis Abu Janjang Kelapa Sawit Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Siska Efendi; Putri Diana; Nasrez Akhir (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
The plant medium condition in the nursery will affect the growth of cacao seedlings. The oil Palm ash is one of the soil ameliorants because it content complete nutrient both macro and micro, the capability to increasing soil pH and having a high base saturation. The objectives of the research were to study the effect of oil palm ash on the growth of cacao seedlings and to get the dose for cacao in nurseries. This research was conducted in experimenta field of 3rd Campus Andalas University Dharmasraya, in December 2018 until March 2019. The experimental method used was a Completely Randomized Design (CRD) consisted of 5 treatments and 5 replications, each of experiment unit consistent of 2 plant polybag so the total of 50 plants was obtained. The Treatments were some doses of oil palm ash of 0 g of oil palm ash/polybag, 150 g of oil palm ash/polybag, 300 g of oil palm ash/polybag, 450 g of palm oil ash/polybag, and 600 g of oil palm ash/polybag. Data analysis was performed by analysis of variance (F test) at the level of 5%. If its results are significant, then further tests with DNMRT at the level of 5%. The results of the present study showed that oil palm ash had an influence on the growth of cacao seedlings on the variables of stem height, stem diameter, number of leaves, and the root length. The dosage of 450 g oil palm ash/polybag showed the best results for stem height and number of leaves of cacao seedlings, while the dosage of 600 g oil palm ash/polybag showed the best results for stem diameter and root length of cacao seedlings. The recommended dose for cacao in the nursery is 450 g of oil palm ash/polybag.